2008
DOI: 10.1177/1077558708319734
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Views on Public Reporting of Hospital Quality Data

Abstract: This article describes physicians' responses to patient questions and physicians' views about public reports on hospital quality. Interviews with 56 office-based physicians in seven states/regions used hypothetical scenarios of patients questioning referrals based on public reports of hospital quality. Responses were analyzed using an iterative coding process to develop categories and themes from data. Four themes describe physicians' responses to patients: (a) rely on existing physician-patient relationships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
3
23
0
1
Order By: Relevance
“…A precondition for this kind of CPI usage is the reliability of the information and its sources. As in other studies, our GPs reported distrust of the content and validity of CPI [16, 23, 25]. As long as GPs do not trust CPI, other sources of information will remain more important in their referral considerations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A precondition for this kind of CPI usage is the reliability of the information and its sources. As in other studies, our GPs reported distrust of the content and validity of CPI [16, 23, 25]. As long as GPs do not trust CPI, other sources of information will remain more important in their referral considerations.…”
Section: Discussionsupporting
confidence: 63%
“…A 1996 study among cardiologists and cardiac surgeons shows that the publication of report cards for grafts bypassing the coronary artery has little credibility and therefore little influence on referral recommendations [25]. A mixed group of physicians described several issues that made them sceptical of the data and concerned about using the information with patients [23]. Further, it appears that quality-of-care data have little impact on referral decisions [22].…”
Section: Introductionmentioning
confidence: 99%
“…This result was consistent with those of previous studies. Barr et al conducted an interview to explore the view of physicians on public reporting and determined that physicians perceived that public reporting lacked methodological rigor [19]. Rechel et al mapped the current approaches of public reporting in 11 high-income countries and learned that the accuracy and reliability of performance data were a main concern of public reporting [20].…”
Section: Discussionmentioning
confidence: 99%
“…Performance reporting and transparency are often regarded as critical components of transforming healthcare. However, it is not clear whether public transparency is more effective than internal publishing of performance data with regard to engaging physicians in quality-and-safety activities 22 23. This is an important area for future exploration, particularly as these data indicate some contention over this issue.…”
Section: Discussionmentioning
confidence: 99%